KINETO-DYNAMIC PADA VARIABLE GEOMETRY SUSPENSION (VGS) - Abdi, Ferly Isnomo; Wasiwitono, Unggul; Arizal, Heru; Ramadani, Ali Hasbi (Universitas Negeri Surabaya, 2021)
Suspension technology on the vehicle provides a comforting effect with shock absorbers and a safety effect in driving and reducing the accident rate. The suspension system was developed by changing the construction and mechanism as well as the addition of a control element. Variable Geometry Suspension (VGS) is the development of a suspension system by using an active actuator is Single-link which is used to change the geometry of the suspension. Geometry change can affect the performance of the suspension system, so a modeling approach is needed to analyze the performance of the VGS system. The VGS modeling uses a quarter-vehicle model and a multi-body model with an equation of motion system using a Kineto-dynamic model with a double-wishbone suspension type. The analysis method on the VGS uses input is bumpy-road to obtain system performance in body acceleration, suspension deflection, and tire deformation. The results of the VGS with the Kineto-dynamic model has a range of 2 mm in the variation of the single-link angle, the performance values ??in the body acceleration and tire deformation between the quarter-vehicle and multi-body models have the same oscillations until steady, while the suspension deflection in the Kineto-dynamic model differs in the first oscillation with a steady time of 1.6 seconds. Therefore, the Kineto-dynamic model can be used to approximate the actual system.